Intervention in the learning process of second year medical students - Fariba Haghani; Atefeh Sadeghizadeh (Journal of Research in Medical Sciences, 2011)
Background: It has been demonstrated that educational programs that focus on study skills could improve learning strategies and academic success of university students. Due to the important role of such supportive programs aimed at the fresh students, this survey was carried out to investigate the effectiveness of an optional course of learning and study skills on learning and study skills of second year medical students. Methods: This quasi-experimental research was performed on 32 eligible medical students in Isfahan University of Medical Sciences, who chose the optional course of learning and study skills. Both of intervention and control groups completed Learning and Study Strategies Inventory (LASSI) at the beginning and the end of semester. Students in the intervention group studied different components of reading and learning skills using team working. Their final scores were calculated based on written reports on application of study skills in exams (portfolio), self-evaluation form and their progress in LASSI test. The mean differences of scores before and after intervention in each of ten test scales were compared between two groups. Results: The results showed that the mean difference scores in attitude, time management, information processing, main ideas selection, study aids and self-testing scales were significantly higher in the intervention group (p < 0.05 for all). Conclusions: This optional course successfully improved learning strategies in the corresponding classroom activities. However, there was no improvement in the motivational scale which is tightly related to the educational success. Therefore, the implementation of educational programs with an emphasis on meta-cognitional aspects of learning is recommended.